Early administration of erythropoietin in extremely very low birth weight preterms - Mihaela Demetrian; Andreea Avramescu; Roxana Iliescu; Andra Pirnuta; Alecsandra Ana Irimie; Vlad Dima (Amaltea Medical Publishing House, 2019)
Objectives. The present study is trying to ascertain if EPO can be administered "early" (before 8 days of life) top revent or reduce the need for blood transfusions. As secondary objectives we aim to observe efficiency and safety when using early EPO with regards to reducing specific ELBW comorbidities. Methodology. Prospective, randomized clinical study, that included 109 preterm babies with GA 30 wk, and BW 1,250 g, born in our unit between January 2018 and June 2019. The treatment we used was early EPO within the first seven days of life, concomitant an oral iron supplement . According erythropoietin therapy, preterms were randomized in EPO group ( n - 40) and control group (n - 69). Results. During hospitalization, there were 51 blood transfusions in the two groups: 13 in the EPO group and 38 in the control group. As for blood transfusions mean, it was 1.1±0.7 for the EPO group (1-3) versus 1.5±1.2 (1-6) for the control group, p 0.25. There were statistically significant differences between the blood transfusions mean volume in the two groups 35.4±19.3 ml for the EPO group versus 53.5±23.8 ml for the control group, p 0.045. There were no significant differences in IVH incidence (> gr. 3) between the two groups. Fisher's exact test showed that there was no influence of EPO on brain hemorrhage (X2 = 0.86, p = 0.38), intestinal tract (X2 = 2.89, p = 1.23), lung tissue (X2 = 0.7, p = 1), or the incidence of retinopathy of prematurity (X2 = 0.42, p = 0.59). Conclusions. In our study, the early initiation of erythropoietin (EPO) at less than eight days, reduced the need for transfusions by 0.5 transfusions/patient. The total volume (ml/kg/patient) of transfused blood was reduced by 18 ml. Although the results from the recent meta-analyzes showed a moderate quality of evidence that EPO reduces intraventricular hemorrhage (IVH), periventricular leukomalacia (PVL) and NEC, the results of our study did not prove this.